Desempenho de longo prazo de IPOs no Brasil: um estudo para o período de 2004 a 2015 - Martins, Fernando Matt Borges (2016)
This study seeks to evaluate the long-term performance of companies that go public in Brazil. The phenomena of (1) underpricing followed by (2) long-run underperformance have been widely documented. The focus of the study is to verify the persistence of the underperformance when lengthened the trial period to five years. In addition, the study aims to evaluate which factors determine the performance in the long run. The study uses a sample of 128 IPOs that went public on the Bovespa stock exchange from 2004 to 2012. The results show statistically significant evidence of underpricing. This underpricing was higher in the years 2004-2008, period before the subprime financial crisis. The results for long-term performance indicate that the portfolio of IPOs had underperformed the market until the 29th month and there is no evidence of persistence of underperformance beyond that month. IPOs launched in the pre-crisis period had underperformed the market after three years, while IPOs launched in the post-crisis had returns above the market for 3 and 5 years. Three main variables were significant in explaining the long-term returns: (1) the launch period of the IPOs, (2) the percentage of allocation to foreign investors, (3) and the reputation of the leader underwriter. IPOs that were launched in the subprime post-crisis period had better performance in the long run. Also the IPOs who had greater percentage of foreign investors showed better performance. In addition, there is an inverse relationship between the reputation of the lead underwriter and the long-run performance.